SOCIAL CLASSES IN THE CANTERBURY TALES - Eldorbek Erkin og’li Khamitov,; Turabayeva Ruhshona O’ktambekovna, (TADQIQOTLAR, 2026)
Abstract This study investigates the representation of social classes in Geoffrey Chaucer’s The Canterbury Tales, focusing on how the work mirrors the hierarchical structure of late medieval English society. Chaucer introduces a diverse cast of characters from various  social  backgrounds,  including  nobility,  clergy,  merchants,  artisans,  and peasants,  offering  a  detailed  and  multifaceted  depiction  of  the  social  order.  Each character’s  story  and  behavior  reflect  their  social  rank,  illustrating  the  values, ambitions, and challenges unique to their class. The analysis explores how Chaucer employs humor, irony, and satire to critique social conventions, reveal hypocrisy, and expose the tensions existing among different social groups. Through the interactions of characters during the pilgrimage, the text reveals  both  the  rigid  structure  and  the  potential  for  social  mobility  in  medieval England. Additionally, the tales shed light on contemporary perspectives regarding wealth,  education,  gender  roles,  and  morality,  providing  insight  into  the  everyday experiences and beliefs of people across social strata. Ultimately, The Canterbury Tales is not only a literary achievement but also a valuable historical source that illuminates the intricacies of medieval social hierarchies. Chaucer’s  work  continues  to  impact  modern  literary  studies  and  social  thought, underlining the importance of understanding class relations through literature.